Kajian Perilaku Masyarakat Pesisir yang Mengakibatkan Kerusakan Lingkungan (Studi Kasus di Pantai Kutawaru, Kecamatan Cilacap Tengah Kabupaten Cilacap) - Luthfi Hidayat Maulana; Andi Hendrawan (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2018)
A coastal area is a transition area between sea and land. The development of the coastal area is influenced by the pressure of human activities and phenomena that occur both on land and sea. The condition is illustrated in the Kutawaru Beach, Bantul District. Kutawaru Beach has a unique nature mainly the pine trees and culinary. However, the behavior of people may endanger the natural condition at this area. The aim of this study is to examine the behavior of coastal communities relates to the environmental damage in Kutawaru Beach and the impact on social and economic aspect. A mixed method was applied by using sequential explanatory design. Selection of the sample is completed by purposive sampling ongovernment and fishermen groups. The results show that the behavior of coastal communities has lead to the environment degradation and it is very influential in decreasing the welfare of society. This research also found that the people's behavior is very much influenced by the little level of education and low awareness on the coastal region of Kutawaru Beach. Local government should work together with the local community to save Kutawaru Beach from environmental damage caused by the behavior of the people themselves.